(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The scientific paper presents a theoretical analysis of scientific sources regarding the effectiveness of therapeutic methods for reducing phantom pain in patients with amputations. To date, phantom pain remains a complex and not fully understood problem, particularly in patients with bilateral amputations. Modern therapeutic approaches to the treatment of phantom pain and the rehabilitation of patients after limb amputation are reviewed. It has been established that existing therapeutic methods are predominantly designed to treat phantom pain in cases of unilateral amputation. The analysis of scientific publications, monographs, peer-reviewed articles, and materials from scientometric databases highlights contemporary methods for overcoming phantom pain, such as motor imagery, mirror therapy (MT), virtual mirror therapy (VMT), and phantom motor execution (PME). The analysis of treatment methods for phantom limb pain demonstrated that phantom motor execution (PME) is the most effective approach, as it provides interactive feedback and enables patients with bilateral amputations to perform real movements of phantom limbs. This method significantly reduces pain intensity and improves the overall condition of patients. Virtual mirror therapy (VMT) and mirror therapy (MT) have also demonstrated effectiveness; however, their advantages compared to PME are limited. Motor imagery has lower effectiveness, as it does not involve interactive tasks or actual motor execution, which limits its applicability for patients with bilateral amputations. Therefore, the use of phantom motor execution (PME) is recommended for reducing phantom pain in patients with bilateral amputations.